2018
DOI: 10.1099/jgv.0.000949
|View full text |Cite
|
Sign up to set email alerts
|

Culex quinquefasciatus mosquitoes do not support replication of Zika virus

Abstract: The rapid spread of Zika virus (ZIKV) in the Americas raised many questions about the role of Culex quinquefasciatus mosquitoes in transmission, in addition to the key role played by the vector Aedes aegypti. Here we analysed the competence of Cx. quinquefasciatus (with or without Wolbachia endosymbionts) for a ZIKV isolate. We also examined the induction of RNA interference pathways after viral challenge and the production of small virus-derived RNAs. We did not observe any infection nor such small virus-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 68 publications
4
27
1
Order By: Relevance
“…These viruses are transmitted by their respective insect vectors in a noncirculative manner (3). In agreement with these findings, we also identified a number of EVEs corresponding to viruses of the Closteroviridae and Bromoviridae families, as well as several other families comprised of viruses not known to replicate outside their plant hosts, including Geminiviridae, quefasciatus (13,14,20). However, it is unclear whether piRNAs are produced from EVEs in nonmosquito arthropod species.…”
Section: Resultssupporting
confidence: 82%
“…These viruses are transmitted by their respective insect vectors in a noncirculative manner (3). In agreement with these findings, we also identified a number of EVEs corresponding to viruses of the Closteroviridae and Bromoviridae families, as well as several other families comprised of viruses not known to replicate outside their plant hosts, including Geminiviridae, quefasciatus (13,14,20). However, it is unclear whether piRNAs are produced from EVEs in nonmosquito arthropod species.…”
Section: Resultssupporting
confidence: 82%
“…They demonstrated that Cx. quinquefasciatus is a competent vector for ZIKV, disagreeing with the findings of Lourenço-de-Oliveira et al [47], who showed that these mosquitoes neither support replication of ZIKV nor play a role in transmission of this virus. Moreover, our study has demonstrated that other species of the Culex genus have vector competence for DENV-2.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies have revealed that EVEs serve as a templates for piRNA production in A. aegypti, A. albopictus , and Culex quinquefasciatus [14, 15, 26], however, it is unclear whether piRNAs are produced from EVEs in non-mosquito arthropod species. We examined the sRNAs mapping to each EVE for the characteristics of primary piRNAs (i.e.…”
Section: Resultsmentioning
confidence: 99%